Oxidative Stress and Related Consequences in Patients with Type 2 Diabetic Mellitus - Iqbal, Nusrum; Khan, Fahad Aman; Khan, Imran; Rauf, Hafiz Abdul; Ahmad, Salman (Journal of Neonatal Surgery, 2025)
Background: An imbalance between biochemical pathways that increase ROS generation and the body's antioxidant defense system causes oxidative stress (OS), a metabolic disorder. It's linked to heart disease, cancer, neurological issues, aging, and respiratory infections. Objective: This study compared persons with and without complications from type 2 diabetes (T2D) in terms of their total antioxidant capacity and total oxidative stress in the blood. Methods: The sample consisted of 80 T2D patients, either with or without subsequent complications. Two groups of participants were formed: those with diabetes (Diab) and those with secondary complications (DSC). To extract serum, blood samples were taken. The colorimetric approach was used to assess the serum samples' total antioxidant capacity (TAC) and total oxidative stress (TOS).SPSS 23.0 was used to analyze all data. Results: Blood glucose and total oxidative stress were considerably (p=0.05) greater in the Diab group than in the DSC group. However, the DSC group's total antioxidant capacity was considerably (p<0.003) lower than the Diab group.Patients with T2D who experienced secondary problems had higher levels of oxidative stress. Conclusion: The conclusion showed that total oxidative stress was higher and total antioxidant capacity was lower in type 2 diabetic patients compared to non-diabetic individuals; this, in turn, causes the development of difficulties related to the disease